2000
DOI: 10.1097/00005537-200007000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Management of Skull Base Osteoradionecrosis

Abstract: Objective: Osteoradionecrosis is one of the most serious complications in radiotherapy ofnasopharyng al carcinoma. We describe a new endoscopic approach to resolve resultant skull base osteoradionecrosis. The objective of this study is to evaluate the fficacy of endoscopic management of skull base ost oradion crosis. Shidy Design: A prospective study of th outcome of endoscopic management for patient with skull base o teoradionecrosis. Methods: Between 1994 and 1998 six patients who had irradiation previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 12 publications
1
45
0
Order By: Relevance
“…3,11 According to reports in the literature, 4,8,11,12 the endoscopic findings, and clinical features, we suggest that the necrosis procedure could be described as 3 stages: (1) early stage: pathologic changes is located in the nasopharyngeal mucosa; local mucosa denaturalization is the primary endoscopic finding; the patients may have a slight headache or not; foul odor is also unnoticeable; (2) middle stage: pathologic changes develop to soft tissue necrosis, including nasopharyngeal mucosa, muscle, and tendon; filemot necrotic tissue is usually found using endoscopy; headache and foul odor are obvious; (3) severe stage: skull base osteoradionecrosis occurs in this stage. Endoscopic examination shows exposed bone or sequestration in the nasopharynx; headache is unendurable if without analgetic, and foul odor is strong and persistent.…”
Section: Discussionmentioning
confidence: 99%
“…3,11 According to reports in the literature, 4,8,11,12 the endoscopic findings, and clinical features, we suggest that the necrosis procedure could be described as 3 stages: (1) early stage: pathologic changes is located in the nasopharyngeal mucosa; local mucosa denaturalization is the primary endoscopic finding; the patients may have a slight headache or not; foul odor is also unnoticeable; (2) middle stage: pathologic changes develop to soft tissue necrosis, including nasopharyngeal mucosa, muscle, and tendon; filemot necrotic tissue is usually found using endoscopy; headache and foul odor are obvious; (3) severe stage: skull base osteoradionecrosis occurs in this stage. Endoscopic examination shows exposed bone or sequestration in the nasopharynx; headache is unendurable if without analgetic, and foul odor is strong and persistent.…”
Section: Discussionmentioning
confidence: 99%
“…The pathologic examination is very important because sometimes it is difficult to differentiate tumor recurrence from ORN or the two pathologic changes existed at the same time during the operation (we had met one patient after a second course of external beam radiotherapy and brachytherapy; his pathologic examination showed ORN with a little of carcinoma nests; this case was excluded). Chang et al 8 reported that MRI could identify ORN and could show the location and extent but could not provide the specific diagnosis. Single photon emission CT could indicate positive results but could not identify the positive scintigram as a specific lesion of ORN; CT was also not reliable.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Patients may have a foul odor, ulceration, repeated bleeding, headache, and nasopharyngeal crust accumulation. 3 Patients with recurrent NPC over the primary site may also have ulceration, repeated bleeding, headache, and nasopharyngeal crust formation, all of which might mimic skull base ORN. Clinically, the differentiation between these two different disease entities remains difficult.…”
Section: Discussionmentioning
confidence: 99%
“…All patients then underwent endoscopic sequestrectomies as we have previously reported. 3 The removed sequestra were sent for pathology verification and determination of the EBV‐derived LMP‐1 gene. After sequestrectomy, all patients still followed a weekly‐based follow‐up protocol until no more bare bone over the skull base was observed.…”
Section: Methodsmentioning
confidence: 99%